Modified Band and Loop Appliance for Retention of Periodontal Dressing on Denuded Bone: A Case Report - Sharma, Shreebindu; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Intraoral lacerations without gape heal spontaneously, whereas lacerations gaping open need to be managed with primary closure or advancement flap. Fall injury leading to a laceration over the left maxillary vestibular region extending till the alveolar ridge with avulsed tooth where primary closure was not possible was planned for debridement followed by periodontal dressing. Due to the lack of retentive area, modified band and loop appliance with a T-loop was fabricated and used for the retention of periodontal dressing for the healing of denuded bone following trauma.